ANALISIS FOUL DAN MOTIVASI PEMAIN MELAKUKAN FOUL DALAM CABANG OLAHRAGA FUTSAL (Studi Kasus Pada Kompetisi Futsal Dies Natalis UNESA Ke-49) - RAHMAD WAKHID, THORIQ (Kesehatan Olahraga, 2014)
THORIQ RAHMAD WAKHID Bobby_trw@yahoo.com Achmad Widodo ABSTRACT The understanding of foul in Futsal is definitely needed by each player to play well. In fact, a lot of Futsal players particularly those who are in Senior High School level often do foul while playing Futsal. Additionally, it is the men players who do foul more often. Thus, the research questions of this study are: (1) how is the understanding of foul of the Futsal players in the competition of the 49th Dies Natalis Unesa? and (2) what is the motivation of the Futsal players to do foul? Therefore, this study aimed at knowing the understanding of foul of the Futsal players in the competition of the 49th Dies Natalis Unesa and the motivation of the players to do foul. This study was a descriptive qualitative study using data collection techniques that were test, interview, and documentation to find out the understanding of foul of the players. Moreover, observation, interview, and documentation (score sheet) were employed to find out the motivation of the players to do foul determined by triangulation data. Based on the interview, it was found that the players did not understand about foul; 3 players did not quite understand, 2 of them understood. In addition, the motivation of the players to do foul was mainly caused by the internal factor that was exhaustion with the total of six times. Keywords : Foul, Understanding, Motivation.